Kinetic Modeling of Direct Methane Chlorination in Both Free-Radical and Catalytic Reactions - Kim, Yeojin; Woo, Yesol; Park, Hyeon; Kim, Youngmin; Chae, Ho Jeong; Park, Myung June (Industrial and Engineering Chemistry Research, 2022)
This paper proposes a kinetic model of the chlorination of methane in the presence of a catalyst. As the reaction involves both gas-phase and catalytic chlorination, the reaction mechanisms with and without the catalyst were considered in this study. Experiments were conducted for the case of the gas phase and with catalysts separately, and kinetic parameters for each phase were estimated independently by fitting the experimental data. The proposed model accurately describes the experimental data (means of absolute relative residual values for the conversions of CH4 and Cl2 and the selectivities of methyl chloride, dichloromethane, and trichloromethane were 9.60, 12.91, 7.79, 19.18, and 16.14%, respectively), in which the presence of the catalyst increased the conversion of methane, while it decreased the selectivity of methyl chloride, which is the desired product in this work. Further analysis showed that a high temperature increased the conversion and reduced the size of the reactor. The production rate of methyl chloride was strongly influenced by the methane fraction in the feed. An optimal fraction exists (70% methane) because an excess amount of methane decreased the conversion. Under optimal conditions, toxic chlorine was completely consumed. It was concluded that the developed model can be used to design an effective reactor for catalytic methane chlorination and determine the optimal operating conditions.
Keywords: Catalytic chlorination; Catalytic reactions; Data mean; Free-radical reactions; Gas-phases; Kinetic models; Kinetics parameter; Methyl chlorides; Reaction mechanism; ]+ catalyst